Prospects for the use of sialylated immunoglobulins in the treatment of different diseases - Yu. V. Markina; A. M. Markin; I. A. Sobenin; A. N. Orekhov (Фундаментальная и клиническая медицина, 2020)
The central role of glycosylation has been well confirmed in numerous studies. In particular, a change in the glycosylation profile of antibodies is observed in infectious diseases, autoimmune disorders and cancer. The analysis of antibody glycosylation can lead to a promising improvement of existing strategies for the disease diagnosis. Specific changes in immunoglobulin glycan molecules can be used in the targeted therapy of multiple diseases, emphasizing the importance of glycans in antibody effector function. Altogether, use of sialylated immunoglobulins may contribute to the next breakthrough in the development of therapeutic drugs and vaccines of the next generation.